2013
DOI: 10.1088/1612-2011/10/5/055805
|View full text |Cite
|
Sign up to set email alerts
|

Multi-walled carbon nanotube as a saturable absorber for a passively mode-locked Nd:YVO4laser

Abstract: Within the family of carbon nanotubes, multi-walled carbon nanotube material has the advantages of low-cost and high laser damage threshold. Therefore, in principle, it is more suitable for high power laser applications. In this letter, a high power continuous wave mode-locking Nd:YVO4 laser using a multi-walled carbon nanotube absorber has been successfully demonstrated. An average output power as high as 1.4 W has been achieved with a slope efficiency of 24%. The repetition rate and pulse width of the mode-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 26 publications
2
7
0
Order By: Relevance
“…The employed MWCNT was grown by electric arc discharge technique, similar to that described in Ref. [27]. The diameter of the MWCNT is about 20-40 nm, and the length distribution is from 1 to 2 μm, with a nonsaturable loss of 12 % and the lifetime of 330 fs [27].…”
Section: Experiments and Discussionmentioning
confidence: 99%
“…The employed MWCNT was grown by electric arc discharge technique, similar to that described in Ref. [27]. The diameter of the MWCNT is about 20-40 nm, and the length distribution is from 1 to 2 μm, with a nonsaturable loss of 12 % and the lifetime of 330 fs [27].…”
Section: Experiments and Discussionmentioning
confidence: 99%
“…Among them, carbon nanotubes are favored as new SA in the field of ultrashort pulse laser due to their excellent electrical, optical, and mechanical properties. According to the number of graphite layers, carbon nanotubes are divided into singlewalled carbon nanotubes (SWCNT) and multiwalled carbon nanotubes [25]. It has been reported that SWCNT-SAs can passively mode lock in 0.8-2-µm laser [26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…The high thermal/laser damage threshold of MWCNT in comparison to that of SWCNTs is because of the added layers of protection against oxidation/damage by the multilayered walls . Although much has been known about MWCNTs, only limited researches reported on the application of MWCNTs as SA. This article was aimed to demonstrate a passively Q‐switched EDFL system using various newly developed MWCNTs‐polymers polyethylene oxide (PEO)‐based SAs as Q‐switchers.…”
Section: Introductionmentioning
confidence: 99%